(untitled) (Conferencea, 2022)
As offspring and creater of the future , the youth play a major role in shaping high society. This article deals with the problems that adults are encountering in the country and some special resolutions to give them all out. This also tries to enaugurate main shifts recorded in Uzbekistan as well as the efforts invested in.